Microstructure and mechanical properties of thermal sprayed nanostructured Cr3C2-Ni20Cr coatings - Cunha,Cecilio Alvares da (2008)
Cr3C2-Ni20Cr coatings have been used for corrosion and wear resistant applications. However, one of the shortcomings of these coatings is its low hardness, and consequent low wear resistance, for long term high temperature applications. Nanostructured coatings of many materials have exhibited higher hardness and strength compared with conventional coatings of the same material. Consequently, nanostructured coatings of other materials, including Cr3C2-Ni20Cr have been attempted to enhance overall performance. In this study the effects of high energy milling parameters on Cr3C2-25(Ni20Cr) powder characteristics as well as the microstructure and mechanical properties of nanostructured Cr3C2-25(Ni20Cr) coatings formed by high velocity oxygen fuel (HVOF) spraying have been evaluated. The average particle size and crystallite size of milled Cr3C2-25(Ni20Cr) powders decreased with increase in milling time and this decrease was more pronounced in nitrogen compared to that in hexane. This difference has been attributed to a cushioning effect in the latter medium. The coatings prepared with milled Cr3C2-25(Ni20Cr) powders had a more uniform microstructure, were harder and had higher relative fracture toughness compared with coatings prepared with as-received powders.